Biopsychosocial impact of high levels of trait anxiety on family caregivers in the end-of-life palliative care setting - Anastasia Maria Grumeth; Hans-Bernd Rothenhäusler; Sabrina Mörkl; Jolana Wagner-Skacel; Elisabeth Sciri; Andreas Baranyi (PLoS ONE, 2025)
Introduction Caring for a family member with a palliative diagnosis at home is physically and mentally stressful. This prospective study explores the emotional and physical burdens experienced by family caregivers in end-of-life palliative care settings, particularly focusing on those caregivers with high levels of pre-existing trait anxiety. The following hypotheses were examined: 1.) Family caregivers with high levels of trait anxiety suffer from high levels of anxiety, stress, burnout symptoms, insomnia, daytime sleepiness, physical complaints, health-related anxiety and resentments. 2.) Caregivers with a high level of trait anxiety are less resilient and receive less social support. They are more likely to use inappropriate strategies in the context of emotional regulation and work-related behavior. 3.) The support provided by the mobile palliative care team reduces stress and improves the quality of sleep of the caregiving relatives. Methods Forty-seven caregivers participated, with assessments conducted at two time points: before the mobile palliative care team’s intervention and six weeks later. Data collection included measures such as the State-Trait Anxiety Inventory (STAI), Whiteley Index (WI), Perceived Stress Scale (PSS-10), Maslach Burnout Inventory (MBI-HSS), Insomnia Severity Index (ISI), Epworth Sleepiness Scale (ESS), Giessen Complaints Questionnaire, Berner Bitterness Inventory (BVI), Brief Resilience Coping Scale, FEEL-E for emotional regulation, AVEM, and the MOS Social Support Survey. Results High levels of trait anxiety among caregivers were significantly associated with increased anxiety, stress, emotional exhaustion, depersonalization, insomnia, and feelings of resentment. Notably, maladaptive emotional regulation strategies were also prevalent. Intervention by the mobile palliative care team significantly reduced stress and insomnia, showing benefits across all levels of trait anxiety. Conclusion Family caregivers with high trait anxiety face significant challenges in end-of-life palliative care settings, indicating a crucial need for early identification and comprehensive biopsychosocial support to mitigate adverse emotional and physical health outcomes.